Formação continuada de professores : análise sobre uso das tecnologias da informação e comunicação - TIC na organização do trabalho pedagógico - Plácido, Maria Elze dos Santos (2011)
This work under the title "Continuing Education of Teachers: analysis of use of information and communication technologies - TIC in pedagogical work organization" is articulated to the Group for Study and Research in Physical Education, Sport and Leisure - GEPEL / UFS, matrix which has as its axis the training of teachers and their significant problems. It is characterized on the one hand, the completion of the Master of the Post Graduate Education - NPGED Federal University of Sergipe - UFS, but on the other, it represents the completion of the investigation process under the significant problem of the formation of teachers against the use of technology applied to education in the organization of educational work. The objective of this study is to analyze the process of continuous training of teachers for the use of information and communication technologies - TIC has qualitatively changed the organization of educational work. The central issue is set to examine how teachers, who participated in continuing education courses offered by the program PROINFO for the use of TIC in education, are appropriating the use of TIC in their teaching. It was hypothesized that continuing education courses whose goal is to empower teachers so that they can adopt information technology and communication in the organization of educational work, has not met its goal. The pedagogical practice shows no qualitative changes expected as information technology and communication have not been used. The reflection on the subject was guided by the understanding that the continued education of teachers in the use of TIC should be understood under the constant link between theory and practice, ie, continuing education within this logic, should provide necessary support for teachers that they can incorporate the use of TIC in their teaching with clarity and in line with the contents worked in the classroom. To realize this research we adopt the type of qualitative research, focusing on methodological dialectical historical materialism. The empirical field of research is the ProInfo Program, offered to schools and teachers in the public municipal office / SE. Being so the case study. The instrument used for data collection was the semistructured interview. The material collected through semi - structured was subjected to content analysis. In this study the data were analyzed under three categories of content: Methods of training courses offered by the program PROINFO; infrastructure of schools, teaching practice. The research result shows that the courses offered by the program PROINFO whose aim is to empower teachers so that they can incorporate the technology into their teaching practices were not always accompanied by a clear and defined policy, much less a knowledge of educational processes and relations and the possible changes caused by these technologies in schools. Although teachers perceive TIC as important tools in education, and have participated in continuing education courses, they do not feel prepared to use them in their teaching, linking it to the contents worked in the classroom.